1976
DOI: 10.3171/jns.1976.45.6.0628
|View full text |Cite
|
Sign up to set email alerts
|

Lateral extracavitary approach to traumatic lesions of the thoracic and lumbar spine

Abstract: The lateral extracavitary approach to the spine was used for resection of displaced bpne and disc located anterior to the dura in 62 patients with traumatic lesions of the thoracic and lumbar spine. Fifty-two patients had closed vertebral fractures and 10 had gunshot wounds. The spinal cord was involved in 44 patients, and the cauda equina in 18. A spinal subarachnoid block was demonstrated in 17 of 57 preoperative gas myelograms. Evoked potential recordings, although related to preception of joint rotation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
88
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(90 citation statements)
references
References 12 publications
0
88
0
2
Order By: Relevance
“…5,[12][13][14]18,34,35,41,43,44,57,59,64 Costotransversectomy was first described by Menard 48 in 1894 for drainage of tuberculous abscesses in patients with Pott paraplegia. Various modifications of this procedure have been developed for removal of anterior thoracic disc herniation, 32,33,40,56,62 traumatic lesions, 40 and metastatic tumors of the spine. 15,55 In the present study we have attempted to elucidate the perioperative complications in patients with thoracic and thoracolumbar neoplasms undergoing either thoracotomy or thoracolumbar approaches compared with costotransversectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[12][13][14]18,34,35,41,43,44,57,59,64 Costotransversectomy was first described by Menard 48 in 1894 for drainage of tuberculous abscesses in patients with Pott paraplegia. Various modifications of this procedure have been developed for removal of anterior thoracic disc herniation, 32,33,40,56,62 traumatic lesions, 40 and metastatic tumors of the spine. 15,55 In the present study we have attempted to elucidate the perioperative complications in patients with thoracic and thoracolumbar neoplasms undergoing either thoracotomy or thoracolumbar approaches compared with costotransversectomy.…”
Section: Discussionmentioning
confidence: 99%
“…When used in conjunction with posterior instrumentation, costotransversectomy has proven to be a successful method in the management of patients with metastatic lesions to the thoracic spine. 5,11,13,14,38,40 In many of these studies the complication rates for costotransversectomies have been reported to be very low. It is difficult to believe that major operations such as costotransversectomies for thoracic neoplasms can be performed with such low morbidity given the significant Neurosurg Focus 11 (6): Article 4, 2001, Click here to return to Table of Contents Perioperative complications with costotransversectomy and anterior approaches to thoracic and thoracolumbar tumors complication rate associated with thoracic pedicle screw placement alone.…”
mentioning
confidence: 99%
“…If so, should Harrington instrumenta tion be combined with decompression, whether from the anterior, the anterolateral, the posterolateral or the posterior approach? (Schmidek et at., 1977;Larson et at., 1976;Riska and Myllynen, 1981;Bohlman and Eismont, 1981;Dolan et at., 1980;Paul et at., 1977;Wang et at., 1979;Young et at., 1981). The purpose of this paper is to report the gradual evolution of a philosophy as it applies to spinal injuries at the thoracolumbar junction.…”
Section: Introductionmentioning
confidence: 99%
“…16 This approach provides dorsal and ventrolateral access to the thoracolumbar spine without the morbidity associated with traditional transpleural and transperitoneal approaches. Additionally, it allows for posterior instrumentation through the same surgical incision.…”
mentioning
confidence: 99%
“…
T he lateral extracavitary approach (LECA) to the thoracolumbar spine was originally described by Larson et al in 1976 for the treatment of traumatic pathology. 16 This approach provides dorsal and ventrolateral access to the thoracolumbar spine without the morbidity associated with traditional transpleural and transperitoneal approaches.
…”
mentioning
confidence: 99%